Innovative practices in ODL — the experience of Open University Malaysia - Chiam , Chooi Chea; Lim, Tick Meng; Phang , Siew Nooi (Asian Association of Open Universities (AAOU), 2012)
With the advancements in communications technology brought about by the advent of the Internet and World Wide Web, attention has been drawn to Open and Distance Learning (ODL) as a mode for teaching and learning. In Malaysia, the establishment of ODL universities such as Open University Malaysia (OUM) has expanded the role of ICT in learning and knowledge generation. By leveraging on Internet technology, ODL universities are able to transmit education across the country and even globally. ODL sets about making quality e-learning and e-content more accessible to both facilitators and learners. Utilising this method, new opportunities are continuously created to make higher education more accessible to those who seek to improve and upgrade themselves. This paper examines OUM's practice of using the innovative technology of online learning and teaching to make higher education easily accessible to those that seek it. With greater advancements in technology, the future of higher education may lie more with ODL than with traditional face-to-face learning.